Source parameter estimation of acoustic emissions induced by hydraulic fracturing in the laboratory. Issue 1 (1st June 2022) - Naoi, Makoto; Imakita, Keiichi; Chen, Youqing; Yamamoto, Kazune; Tanaka, Rui; Kawakata, Hironori; Ishida, Tsuyoshi; Fukuyama, Eiichi; Arima, Yutaro
SUMMARY: The hydraulic fracturing technique is used for resource production, such as in shale gas/oil extraction and enhanced geothermal systems. The effects of fracturing are often monitored via induced earthquakes, and obtaining as much information as possible from those earthquakes is desirable. The stress drop—calculated from the seismic moment M o and corner frequency f c —is an earthquake-related parameter that can help identify additional characteristics of the seismicity. To investigate the relationship between stress drops and hydraulically induced seismic events, we estimated the M o and f c of acoustic emission (AE) events during hydraulic fracturing experiments performed in the laboratory in previous studies using 2 Eagle Ford shale and 10 Kurokami-jima granite samples. We estimated M o by fitting the theoretical spectra to the observed spectra after correcting for the following effects: (1) frequency response of AE transducers under the installation method used in the fracturing experiment, including differences in sensitivity across every transducer used in each experiment; and (2) the difference in radiation pattern coefficients, which depends on the focal mechanisms of each AE event. This analysis used 46 857 focal mechanisms obtained from moment tensor solutions estimated using a deep learning technique. The range of the resultant M o was found to be 2.8 × 10 –5  ≤  Mo  ≤ 4.5 × 10 –1 [N·m], corresponding to −9.1 ≤  M w ≤ −6.3, where M w is the moment magnitude. We also estimated f c using the multiple-empirical Green's function method, reducing the influence of modelling errors in the AE sensor response and transfer function of the medium. Out of the 1053 events whose M o and f c were estimated, 465 events (44.2 per cent)—regardless of their focal mechanisms—were found to have M o and f c values consistent with the constant stress drop scaling of shear failure (i.e. shear failures have 0.1–100 MPa stress drops independent of their magnitude) that has been repeatedly confirmed in many previous studies. The remaining events showed lower f c values than those expected from the scaling law. This indicates that high pore pressure in a source region induced by fluid stimulation contributes to the occurrence of low-frequency earthquakes. Overall, we demonstrated that source parameter estimation was possible for laboratory AEs induced by hydraulic fracturing, which can improve our understanding of the characteristics of fluid-induced earthquakes.